KAJIAN BUDIDAYA TANAMAN PALA (Myristica fragrans Houtt) DI KABUPATEN KEPULAUAN SANGIHE - Widia L. Legoh; Deanne Kojoh; Semuel Runtunuwu (Universitas Sam Ratulangi, 2017)
ABSTRACT This study aims to determine the nutmeg crop cultivation techniques carried out by farmers in Sangihe Islands Regency. This research is a quantitative data of collection techniques using a structured questionnaire to collect data on the cultivation of nutmeg applied by farmers, from seeding to the control of pests and diseases. Farmers surveyed 150 people, divided into three sub-district in the District of West Tahuna, Manganitu and Kendahe.Â Determination of farmers in every village performed by using the